Pengaruh Sosial dan Reputasi Lembaga terhadap Keputusan Muzaki ASN dalam Pembayaran Zakat melalui Sistem Pemotongan Gaji di BAZNAS Kabupaten Mojokerto dengan Religiusitas sebagai Variabel Moderasi - Hida Wahyukharisma Putri; Nurwinsyah Rohmaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of social factors and institutional reputation on the decisions of civil servant (ASN) muzaki, as well as to examine the role of religiosity as a moderating variable. This research employed a quantitative approach with an associative research design. The sample consisted of 130 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that social influence, institutional reputation, and religiosity have a positive and significant effect on muzaki decisions. Religiosity is proven to moderate the influence of social factors on muzaki decisions, but it does not moderate the influence of institutional reputation. This study confirms that ASN's zakat decisions are influenced by social norms, religiosity, and institutional reputation, so it is necessary to strengthen the social environment, institutions, and religious values.